PEMANFAATAN GOOGLE CLASSROOM SEBAGAI ALTERNATIF TAMBAHAN MEDIA PEMBELAJARAN SECARA DARING BAGI GURU DAN SISWA DI SMK NEGERI 7 KOTA SERANG - Fauzan Dika; Rimasya Ayu Jaeningsih (Abdi Jurnal Publikasi, 2024)
In accordance with developments in the current era of disruption 4.0, namely teachers in the future This must be able to present learning modules that are easy to apply, in this era As technology advances, the modules used in Learning does not always use conventional modules. Just a teacher The future must be able to present learning material in the form of modules which can be accessed online by students. Future teachers must be capable presents learning that combines hands on and mind on, problem based learning and project based learning. Google Classroom for Education is one features of Google products that can be used as alternative media online learning at school, with the various features it has. This PkM aims to determine the success of Google Classroom as online learning media at SMK Negeri 7 Serang City. Next destination is to measure the ease and obstacles of learning to use Google Classroom as an alternative online learning model for the eyes certain lessons at SMK Negeri 7 Serang City. subject of This service is for teachers and students of SMK Negeri 7 Serang City with using two methods, namely qualitative with results data collection techniques observation of recording case studies of the application of Google Classroom and quantitative with data collection techniques, literature studies, observation, media creation and questionnaire. It is hoped that the results of this service activity will produce teachers who are able to design learning by utilizing Google Classroom for Education as a blended learning media and students who can access the reach of independent learning anywhere, both online and offline.